2010
DOI: 10.1080/10410230903473532
|View full text |Cite
|
Sign up to set email alerts
|

Message Framing and Defensive Processing: A Cultural Examination

Abstract: Past research has shown that health messages on safer sexual practices that focus on relational consequences are more persuasive than messages that focus on personal consequences. However, we theorize that it is defensiveness against personal risk framing that threatens the self among people from more individualistic cultures. Two studies tested this idea. Study 1 showed that European Americans were less persuaded by personal framing than by relational framing but that this pattern was not found for Asian Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Some show an increase in risk perceptions in response to a threatening message (Harris & Napper, 2005;Sherman et, al. 2000) but several others have not (e.g., Harris, Mayle, Mabbott, & Napper, 2007;Klein & Monin, 2009;Ko & Kim, 2010;Napper et al, 2009) or have found that for some individuals it can decrease risk perceptions (e.g., non-defensive individuals; Griffin & Harris, 2011;). These mixed findings provide even more evidence of the need to establish whether self-affirmation may have more reliable effects on feelings of vulnerability, and whether such effects mediate concomitant effects of self-affirmation on behavioral intentions.…”
Section: Feelings Of Vulnerability As Mediating Mechanismmentioning
confidence: 95%
“…Some show an increase in risk perceptions in response to a threatening message (Harris & Napper, 2005;Sherman et, al. 2000) but several others have not (e.g., Harris, Mayle, Mabbott, & Napper, 2007;Klein & Monin, 2009;Ko & Kim, 2010;Napper et al, 2009) or have found that for some individuals it can decrease risk perceptions (e.g., non-defensive individuals; Griffin & Harris, 2011;). These mixed findings provide even more evidence of the need to establish whether self-affirmation may have more reliable effects on feelings of vulnerability, and whether such effects mediate concomitant effects of self-affirmation on behavioral intentions.…”
Section: Feelings Of Vulnerability As Mediating Mechanismmentioning
confidence: 95%
“…In spite of the support for the congruency hypothesis, other studies have suggested that matching message focus with people's cultural orientation might not necessarily increase the persuasiveness of a health message. Specifically, scholars found that when a culturally matched message contained negative or threatening health information, the message may become less effective (Ko and Kim, 2010). Previous research suggested that people have self-serving bias and tend to process personally relevant messages that are intimidating in a biased manner (Kunda, 1987).…”
Section: Independent Vs Interdependent Self-construalmentioning
confidence: 99%
“…Empirical evidence on the impact of eliciting positive emotions to promote behavior change is scant particularly on changes that do not directly impact the individual. The potential impact of messages that aim to facilitate emotional reactions and processing of those emotions should be carefully considered (Cameron and Chan, 2008;Ko and Kim, 2010). Taken together, a presenter who gets to know the target audience, focussing on the local and targeting aspects of TLC4 in advance, should be able to craft a balanced and believable presentation that maximizes the benefits of emotion to drive altruistic behavior change benefiting people with mental health conditions.…”
Section: Engaging Emotionsmentioning
confidence: 99%